André Frénaud's Plural Voice - Roger Little (Studies in 20th & 21st Century Literature, 1989)
Dramatic self-projection and the use of recurrent or occasional personae are features manifest in André Frénaud's poetry. One also notes a tendency to multiply unique phenomena. Furthermore, the medium of his poetry displays huge variety in form and tone. This study reviews a selection of these interacting characteristics and investigates their relationship to the poet, who represents the unity beneath the diversity, but whose self proves versatile in its exploration of world, word and identity through the revealing ventriloquy of plural voices.
Keywords: André Frénaud; poetry; French poetry; self-projection; poetic variation; unique phenomena; identity; plural voice; voice